2021
DOI: 10.1097/ede.0000000000001430
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Exposure to Air Pollution and Attributable Risk of Kidney Diseases

Abstract: Background: Several studies have shown that long-term exposure to air pollution is associated with reduced kidney function. However, less is known about effects of short-term exposure to air pollution on kidney disease aggravation and resultant emergency room (ER) burden. This study aimed to estimate excess ER visits attributable to short-term air pollution and to provide evidence relevant to air pollution standards to protect kidney patients. Methods: We conducted time-series analysis using National Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Third, because this study was conducted in the Republic of Korea, a practically single-ethnic nation, caution should be exercised in generalising the results to other populations, given the potential heterogeneity of the results by race/ethnicity suggested by previous studies 43. Fourth, there is a concern of exposure misclassification attributable to large spatial units, although several time-series studies conducted in Korea used regional air pollution levels as exposures (instead of air pollution levels measured for a finer spatial unit) 44–46. This type of error (ie, Berkson error) is likely to lead to imprecision in the estimation of associations rather than bias.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Third, because this study was conducted in the Republic of Korea, a practically single-ethnic nation, caution should be exercised in generalising the results to other populations, given the potential heterogeneity of the results by race/ethnicity suggested by previous studies 43. Fourth, there is a concern of exposure misclassification attributable to large spatial units, although several time-series studies conducted in Korea used regional air pollution levels as exposures (instead of air pollution levels measured for a finer spatial unit) 44–46. This type of error (ie, Berkson error) is likely to lead to imprecision in the estimation of associations rather than bias.…”
Section: Discussionmentioning
confidence: 98%
“…43 Fourth, there is a concern of exposure misclassification attributable to large spatial units, although several time-series studies Open access conducted in Korea used regional air pollution levels as exposures (instead of air pollution levels measured for a finer spatial unit). [44][45][46] This type of error (ie, Berkson error) is likely to lead to imprecision in the estimation of associations rather than bias. Fifth, we only considered three criteria air pollutants (ie, PM 2.5 , NO 2 and O 3 ) as exposures according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large time-stratified case-crossover study in the US Medicare population showed that each 10 µg/m 3 increase in PM 2.5 was associated with a 2.3% (95% CI: 1.7% to 3.0%) relative increase in the risk of acute and unspecified renal failure hospital admission [ 3 ]. Other time-series studies that investigated associations between short-term exposure to air pollution and emergency department visits for kidney diseases in North American and East Asian population reported relative percent changes ranging from 10% to 3.4% [ 1 , 2 ]. Another time-stratified case-crossover study in Hubei province of China estimated that each 10 µg/m 3 increase in PM 2.5 , PM 10 , and NO 2 was associated with a 4.14% (95% CI: 1.25% to 7.12%), 2.67% (95% CI: 0.80% to 4.57%), and 1.46% (95% CI: 0.76% to 2.17%) increase in odds of myocardial infarction mortality [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence has shown that both shortterm and long-term exposure to air pollution is associated with kidney outcomes [1][2][3][4][5][6][7]. A few time-series studies reported positive associations between shortterm exposure to air pollution and emergency department visits or hospitalizations for kidney diseases in North American and East Asian populations, and the risk ratios ranged from 1.010 to 1.034 [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation